Effect of Severe Acute Respiratory Syndrome Coronavirus 2 on Blood Product Utilization in the Community Hospital Setting. (28th October 2021) - Messersmith, L; Mack, M; Cordell, J
Abstract: Introduction/Objective: Blood products are a major expense for the laboratory, with an intricate balance between maintaining adequate supply and expiring products. Blood product wastage rates are typically less than 2%. The SARS-CoV-2 (SARS-CoV-2) pandemic has created a multifaceted challenge in blood utilization. Difficulties in predicting product usage, decreased supply, and transportation delays put hospitals at risk of increased blood product destruction. In this study, we analyze the effect of the SARS-CoV-2 pandemic on blood utilization in the community hospital setting, in order to develop improved laboratory management strategies for decreasing unit wastage. Methods/Case Report: Quality indicators of blood utilization from 2012 to 2021 were retrospectively reviewed. Data was collected for packed red blood cells (pRBCs), platelets, and plasma. Units transfused, expired/destroyed, and total percent discarded were recorded for each month. Average transfusion and destruction rates were calculated for each product. Blood product utilization from 2020 was compared to years 2012-2019 using Pearson correlation, linear regression, and student paired t-tests. Results (if a Case Study enter NA): 1, 042 units were reviewed. For pRBCs, there was a strong correlation between 2020 and increased destruction compared to 2012-2019 (R= 0.8, p=0.005). There was no significant change in pRBC transfusions in 2020 compared to 2018 and 2019 (p= 0.3, p= 0.2). There were fewer pRBC transfusions in 2020 compared to 2016 and 2017 (p= 0.006, p=0.01). For platelets, there was increased destruction in 2020 compared to 2012-2019 (p= 0.01-0.04) and no significant change in usage (p= 0.3-0.5). Conclusion: During the 2020 SARS-CoV-2 pandemic, there was a significant increase in blood product wastage. There was no significant increase in transfused pRBCs or platelet units, suggesting the increased destruction was not due to an overall increase in transfusions. Blood products are a major cost for laboratory and further investigation of these findings is warranted to mitigate continued wastage.